A continuum damage mechanics approach coupled with an improved pit evolution model for the corrosion fatigue of aluminum alloy. (December 2016) - Hu, Ping; Meng, Qingchun; Hu, Weiping; Shen, Fei; Zhan, Zhixin; Sun, Linlin
Highlights: An improved pitting evolution model is proposed for pit growth. The effects of multiaxial stress and fatigue damage are considered in pitting. A continuum damage mechanics model is adopted to evaluate fatigue damage. The proposed approach is validated by the experimental results. The interaction between corrosion and cyclic stress is presented. Abstract: In this study, a continuum damage mechanics approach coupled with an improved pit evolution model was proposed to predict the corrosion fatigue life of aluminum alloy. The coupled elasto-plastic damage constitutive equations and elastic–plastic damage evolution models were adopted to evaluate the fatigue damage. Pit growth was modeled with considering the effects of multiaxial stresses and fatigue damage. Numerical simulations were then implemented using the ABAQUS, and the results were compared with the experimental data. In addition, the interaction between corrosion and fatigue damage was presented, and the effects of the stress level and loading frequency were examined.